Penyimpangan Distribusi Obat Keras pada Sarana Tidak Memiliki Keahlian dan Kewenangan Melakukan Praktik Kefarmasian: Indonesia - Rizki Arrahman Yovia; Fauqi Elfarabi; Fuji Handayani; Ari Andriano Santoso; Surya Dwi Putra (Eruditio : Indonesia Journal of Food and Drug Safety, 2021)
The distribution diversion of prescription drugs at facilities that do not have the expertise and authority to pharmaceuticals practice dominate other types of violations, they are Illegal Drugs and Substandard Drugs. This phenomenon is also caused by public participation, the tendency of people who want to do self-medication, ease of transaction, efficiency of time, energy, and the changes of lifestyle are factors that support the rapid growth of commerce transactions through offline and online media. This trend will certainly have a major impact on the supply chain, especially on drug distribution in Indonesia. The research used qualitative and quantitative methods to obtaining an overview of drug distribution that could describe the situation of supply chain, the potential, and spot that could be used as a diversion of the distribution of prescription drugs in facilities that do not have the expertise and authority to pharmaceuticals practice. The results showed that 90.3% of drugstores sell prescription drugs with the modus dominated by salesmen at 88.4%. Drugstores that selling prescription drugs generally does not put up a drugstores name sign (28.93%). Distribution Systems of prescription drugs at facilities that do not have the expertise and authority to pharmaceuticals practice is carried out offline and online that makes the drug marketing become wider. The diversion of prescription drug distribution occurs in the process of importing medicinal ingredients, the pharmaceutical industry, and retail facilities.